Interleukin-4 and -13 expression is co-localized to mast cells within the airway smooth muscle in asthma. - Brightling, C; Symon, F; Holgate, S; Wardlaw, A; Pavord, I; Bradding, P (2003)
BACKGROUND: Airway smooth muscle infiltration by mast cells is a feature of asthma and not eosinophilic bronchitis. In asthma, Th2 cytokines have been implicated as playing a critical role in the development of airway inflammation and hyper-responsiveness. Whether inflammatory cells within the airway smooth muscle release these cytokines is unknown. METHODS: We have undertaken a comparative immunohistochemical study in bronchial biopsies from 14 subjects with asthma, 10 with eosinophilic bronchitis and eight normal controls recruited from two centres. RESULTS: The median number of IL-4+ cells/mm2 smooth muscle was significantly higher in subjects with asthma than eosinophilic bronchitis and normal controls for both the anti-IL-4 mAb 3H4 (2.4, 0, 0, respectively; P=0.001) and anti-IL-4 mAb 4D9 (1.6, 0, 0, respectively; P=0.02). There were no group differences in the number of IL-5+ cells (P=0.31). In six subjects with asthma, IL-13 expression by cells within the airway smooth muscle was studied. The median (range) of IL-13+cells was 2 (0.9-2.7). Ninety-four percent of the cells expressing IL-4 (3H4), 92% of those expressing IL-4 (4D9) and 100% expressing IL-13 in the airway smooth muscle were mast cells. Fifty-five percent of the mast cells within the airway smooth muscle co-localized to IL-4 (3H4), 29% to IL-4 (4D9) and 17% to IL-13. CONCLUSIONS: In asthma, IL-4+ and IL-13+ cells were present within the airway smooth muscle and were expressed predominantly by mast cells, suggesting that IL-4 and IL-13 may play an important role in mast cell-airway smooth muscle interactions.